The Influence of Agricultural Environment on Inflammation and Breast Cancer: A Systematic Review - Abdussalam, Arrizqi Hafidh; Permatasari, Happy Kurnia; Sutrisna, EM.; Romadhon, Yusuf Alam; Kurniati, Yuni Prastyo (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Analyzing the influence of agricultural environment on inflammation and breast cancer. Methodology: PECOS by mentioning terms in MeSH as search keywords. Inclusion criteria include: observational cohort, cross sectional or case control study design. Exclusion criteria included various forms of reviews, experimental design studies, RCTs and in animals, in-vitro studies and in-silico studies. Results: Google Scholar platform search obtained 112 articles and 177 articles from the Scopus database. After identification and screening using PRISMA-P, 6 articles were obtained. Benign and malignant breast lesions were significantly associated with exposure to environmental estrogens including polychlorinated biphenyls (PCBs) and organochlorines. There was an increase in inflammatory biomarkers, namely NF-κB, PPAR-γ, IL-12 dan TNF-α levels in breast lesions from areas with high pesticide spending. Applications: The agricultural environment is a risk factor for breast cancer mediated by inflammatory factors.